Doctrinal difference in the issue of resurrection and the field of tolerance - Sadeq Kazem Maklef ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Islamic religion emphasized on the basis of tolerance and forgiveness in all aspects of life, because of its great importance in building society and preserving its unity, and among the basics of thought and reason produces different opinions and ideas, which seem to provoke difference and disunity apparent, but they are natural things for human thought and a positive evidence of activity Intellectual and mental in humans, provided that it does not deviate from the paths of righteousness and leads to the destruction of society with negative thoughts.As for the opinion of some Islamic philosophers and some theologians, and when they have contradicted the consensus and what the explicit Islamic texts indicate from the Qur’an and Sunnah regarding the resurrection of the soul and the body together, and then they have violated this necessity of the necessities of the Islamic religion, then according to this criterion they are outside Islam and condemn the body disbelief.However, by reviewing the opinions of Islamic scholars, especially the contemporary ones, we find that they have left room for tolerance to flow in.Among that difference is the doctrinal difference that dealt with the issue of the Resurrection as a model for that, which is one of the most prominent and most important doctrinal issues in Islam, and Muslim thinkers have been interested in researching this issue greatly through the many effects, and I showed the opinions that dealt with this issue in brief, then we dealt with the field of tolerance With that difference in the true Islamic religion and the extent of the impact of tolerance on the intellectual construction and advancement of society, especially since thinking and knowledge research has a great role in building and progressing.The research was divided into an introduction, a preface, four chapters and a conclusion, and it relied on the sources of language, speech, philosophy and related sources.DOI /10.54633/2333-021-042-019